2021
DOI: 10.1371/journal.pone.0249198
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 3-month mortality in bedridden patients with hospital-acquired pneumonia: A multicentre prospective study

Abstract: Background Mortality among patients with hospital-acquired pneumonia (HAP) is quite high; however, information on risk factors for short-term mortality in this population remains limited. The aim of the current study was to identify the risk factors for mortality in bedridden patients with HAP during a 3-month observation period. Methods A secondary data analysis was conducted. In total, 1141 HAP cases from 25 hospitals were included in the analysis. Univariate and multilevel regression analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…It is noteworthy that, among men, those who underwent surgery had lower risk of IHM, a finding previously described by other authors [1]. The reason may be that one of the most important surgical indications is a relatively good baseline health condition [34]. Therefore, the physical condition of these patients may be better than that of patients who cannot undergo general anesthesia, and they are less likely to suffer pneumonia infection because of their suitability for more comprehensive treatment and care, such as sputum aspiration after completion of general anesthesia surgery [35].…”
Section: Discussionsupporting
confidence: 58%
“…It is noteworthy that, among men, those who underwent surgery had lower risk of IHM, a finding previously described by other authors [1]. The reason may be that one of the most important surgical indications is a relatively good baseline health condition [34]. Therefore, the physical condition of these patients may be better than that of patients who cannot undergo general anesthesia, and they are less likely to suffer pneumonia infection because of their suitability for more comprehensive treatment and care, such as sputum aspiration after completion of general anesthesia surgery [35].…”
Section: Discussionsupporting
confidence: 58%
“…Regarding the context, we observed that a large number of studies were performed in research institutes with healthy controls; thus, at the time of publication of these studies, the respective programs were not yet implemented in a clinical context. On the other hand, this also demonstrates the importance of performing preclinical and clinical studies with healthy individuals [ 55 , 56 ] to access the rehabilitation program’s safety, since bedridden persons are often in a great state of fragility with a considerable variety of diseases and comorbidities [ 13 , 14 ]. A large number of studies were also performed in a hospital context.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of complications of immobility on patients’ overall well-being and functioning is a topic of growing interest in clinical research and practice [ 6 , 13 , 14 ]. Providing effective care, such as early rehabilitation, appears to hold promise in preventing disuse syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Without timely and appropriate treatment, patients with HP will die of multiple organ failure ( Traver, 1974 ). It was reported that pneumonia causes 68.1% of deaths in bed-ridden patients within half a year, and the 3-month mortality of bed-ridden patients with merely one of the leading HP was 16.56% ( Kosaka et al, 2012 ; Jiao et al, 2021 ). According to current standard practice, pathology specimens of patients with HP are assessed for the presence of bacteria or viruses, paying little attention to other pathogens ( Koechlin et al, 2014 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%